Concepções epistemológicas subjacentes às falas e práticas pedagógicas de professores que ensinam Matemática nos anos iniciais do ensino fundamental - Cardoso, Evanil de Almeida (2017)
This research has as its title; Epistemological conceptions underlying the speeches and the pedagogical practices of teachers who teach mathematics in the early years of Elementary School. Its object of study is the Teachers‟ epistemological concepts. This research aims at analyzing the influence of epistemological conceptions concerning Mathematics in the pedagogical practice of the educators who teach at the initial years of the Elementary School. The investigations were carried out on the scope of the epistemological conceptions of teachers and the teaching of mathematics in the initial years of Elementary School have revealed that their conceptions are based on the idea of a conceptual essence which determines the teachers‟ thoughts and actions. This essence constitutes the teachers‟ way of thinking, seeing, and organizing the world. The comprehension of the epistemological conceptions requires an interpretive reading of different understandings of knowledge. The contents of mathematics, demands mathematics teachers who present the mathematics to their students as a science that does not deal with eternal infallible and immutable truths, but as a dynamic science, open to the incorporation of new knowledge. The epistemological conceptions or theory of knowledge presuppose the understanding of their implications on the different theoretical approaches, and also their importance and contribution. This research emphasizes the Piagetian‟s theory, which is based on the understanding that learners learn through their own actions on objects, build their own categories of thought at the same time that they organize their world. The constructivist theory based on Piaget‟s thoughts defends the idea that the structures of thinking, judging and arguing result from a permanent work of reflection and reassembly, the perceptions that the child has, acting on its physical world and interaction with other people in its social world. The authors who guide this study are: Hessen (1976), Piaget (2007), Moreira (1999), Becker (1998, 2001; 2011; 2012), D'Ambrósio (1986; 1999; 2007), Kamii (2004), Nunes (2007), Darsie (1998; 1999), among others. It was opted for the qualitative research and interpretative method to analyze the interviews of four pedagogical teachers who teach for children‟ classes in the third, fourth and fifth years of Elementary School in two schools in the city of Cáceres, in the state of Mato Grosso, in Brazil. This research counted on as instruments: the observation of the classes, interview and analysis of documents – teachers lesson plans. The categories which anchor the analysis were: 1. The relation of the epistemological conceptions and the pedagogical practice; 2. The most frequent conception in the teachers‟ practice; 3. Situations that show or reveal teachers' conceptions; 4. Interlacing conceptions: the search for an understanding about the theme. This research presents the following findings: the studied teachers use their conceptions acquired at the time of their basic and initial formation to guide their pedagogical practice in the classroom. It is concluded that the underlying conceptions are not always evident in the teachers' speeches. Their conceptions are manifested with greater intensity in their pedagogical practice. Their reflection, at the moment of continuous formation are manifested as a component for overcoming crystallized conceptions. It is assumed that the epistemological conceptions present in teachers' speeches and in their pedagogical practice have a determining influence on their act of teaching mathematics in the early years of their Basic Education. In this sense, this research constitutes a path with many possibilities for discussions and recommendations to a meaningful, pleasant and efficient pedagogical practice.